Praktek Larangan Perkawinan di Antara Dua Hari Raya (1 Syawal-10 Zulhijah) Perspektif Hukum Islam - Mustafid Mustafid (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This research examines Islamic law's view regarding the prohibition of marriage between two holidays (1 Shawwal-10 Dhu al-Hijjah) in Sungai Apit Village and the nature of the prohibition on marriage in Islam. The method in this research is normative with a sociological and phenomenological approach. The results of this research data show that the reasons behind the emergence of a ban on marriage between two holidays (1 Syawal-10 Dhu al-Hijjah) are first, the majority of Sungai Apit people have migrated to Malaysia and will only return home when the Eid al-Adha holiday approaches. Second, traditional leaders understand that the prohibition on marriage is surrounded by two holidays considered sacred by the community and are not allowed to disturb their sacredness. Third, the people of Sungai Apit from 1 Shawwal to 10 Zulhijah focus on increasing the amount of worship that can only be done at that time. Fourth: customs created for the good of society. As for the review of Islamic law, the prohibition of marriage between two holidays (1 Shawwal-10 Dhu al-Hijjah) is contrary to Islamic law because custom has prohibited something permitted in Islam; even the month of Shawwal is the recommended time for marriage. So, for people who marry between two holidays, the law is permissible.